Sovereignty – of God, the nation, the people? Distinction and ambiguity - von Sinner, Rudolf (Stellenbosch Theological Journal, 2025)
Starting with an analysis of recent examples of Christian exponents trying to influence government in South Africa and Brazil, the article recalls the confessional declarations of Barmen, Belhar, and against the russkii mir, in their advocating a sovereign God against a totalitarian regime. While this shows efficient in specific historical circumstances, it is insufficient in a secular, religiously diverse environment. God’s sovereignty is not only questioning human sovereignty, but tempers the concept itself. Rather than an oppressive “monotheism of truth”, it is a “monotheism of loyalty” (Jan Assmann) in God’s covenant with the people that presupposes their consent and the giving of the law. “The people” are, however, a precarious category and reality, given the ambiguity of good and evil as present in the world, which does not leave Christian communities untouched. This should produce a more humble approach that seeks to formulate a new, relational and dynamic concept of God’s sovereignty that has its bearing on people’s sovereignty as they are bound together in a covenantal relationship governed by the law.